ChemInform Abstract: Co2(CO)8‐Mediated Selective Reductions of Propargyl Alcohol Derivatives to Alkenes. Issue 12 (March 2015) - Dou, Ying; Xing, Ping; Huang, Zuogang; Jiang, Biao
Abstract The Z/E selectivity of the title reduction reaction is influenced by the type and amount of an additive.